Pegfilgrastim Biosimilars: Where Are We Now? - Selby, Christopher (J Adv Pract Oncol, 2021)
In 1991, the U.S. Food & Drug Administration (FDA) approved rmetHuGCSF for human use. This recombinant methionyl human granulocyte colony-stimulating factor, or filgrastim, saw use in over 1 million patients in its first 5 years on the market. In 2002, the FDA approved a version of filgrastim with covalent linkage to a monomethoxypolyethylene glycol, increasing the molecular size and half-life to replace multiple days of dosing with a single injection. These medications remained standard of care for neutropenia until the Biologics Price Competition and Innovation Act of 2009 created an abbreviated pathway to licensure for biologic products. Practitioners now have their pick of numerous and expanding options for pegfilgrastim biosimilars.